The impact of audit committee characteristic on firm performance of Malaysian consumer products and services companies - Lau, Careine; Chong, Sin Jie; Koh, Ming Shuang; Lim, Hew Thong; Sim, Soon Ket (2022)
The purpose of this study is to analyze the impact of audit committee characteristics on firm performance. Due to some data omission, 163 out of 187 consumer products and services companies listed in Bursa Malaysia were sampled and the sampling period was from 2015 to 2019. In this study, size of audit committee, competency of audit committee, frequency of audit committee meeting, and gender diversity of audit committee are applied as independent variables while board size, firm size, and total debts are applied as control variables to investigate their effects on firm performance. Since there are different measures of the dependent variable, which is firm performance, this study is divided into two models, Model 1 for Return on Assets and Model 2 for Economic Value Added. The result of this study shows that size of audit committee, board size, firm size, and total debts have insignificant impact on firm performance in both Model 1 and Model 2. Whereas the competency of audit committee and gender diversity of the audit committee have a significant effect on firm performance in Model 1, while in Model 2 the effect is insignificant. The frequency of audit committee meetings shows an insignificant result in Model 1 and a significant result in Model 2. This study contributes to companies, regulators and policy makers, shareholders and investors, and academicians and future researchers as an informative study on the influences of audit committee characteristics on firm performance.